Microdytes huangyongensis sp. n. and new records of Allopachria Zimmermann, 1924 from Zhejiang Province, China (Coleoptera: Dytiscidae) - Bian, Dongju; Zhang, Yue; Ji, Lanzhu (Zootaxa, 2015)
An excursion to Zhejiang, China was made in August 2014, and two species of Microdytes J. Balfour-Browne, 1946 (M. uenoi Satô, 1972 and M. huangyongensis sp. n.) and two species of Allopachria Zimmermann, 1924 (A. miaowangi Wewalka, 2010, and A. schoenmanni Wewalka, 2000) were collected. Only one species of Microdytes (M. uenoi Satô, 1972) was recorded from Zhejiang before. The genus Allopachria is reported from Zhejiang for the first time. The genus Microdytes occurs throughout southern and south-eastern Asia. Since the revision of Microdytes by Wewalka (1997), sixteen new species and one new synonymy have been reported (Wewalka 1998; Wewalka & Wang 1998; Wewalka et al. 2007; Bian & Ji 2009; Miller & Wewalka 2010; Wewalka 2011). Including the new species the genus Microdytes comprises 46 species.